Management Strategies For Implementing Zero Waste Practices in Food and Beverage Operations: Perspectives From Hospitality Management Students at Dhyana Pura University - Sulistyo, Eko; Suartana, I Ketut (Jurnal Manajemen Pelayanan Hotel, 2024)
Integrating zero waste practices in food and beverage operations is vital for promoting sustainability in the hospitality industry. However, effective management strategies for implementing these practices remain underexplored, particularly from the perspective of future professionals. This study investigates hospitality management students' perceptions of management strategies for zero waste implementation at Dhyana Pura University. Utilizing a mixed-methods approach, the research surveyed 25 students from the Hospitality Management Study Program to quantitatively assess their awareness, attitudes, and perceived effectiveness of various management strategies. In-depth interviews provided qualitative insights into students' experiences and expectations regarding management's role in facilitating sustainable practices. Findings indicate that students recognize the importance of strong management support and strategic planning in addressing challenges such as resource limitations and staff training. While students’ express optimism about the benefits of zero waste practices, they also emphasize the need for practical training and real-world applications to enhance their readiness for future careers. In conclusion, the study highlights the need to incorporate effective management strategies into hospitality education to better prepare students for implementing zero waste practices. Recommendations include developing curriculum modules focused on sustainability management strategies and fostering partnerships with industry stakeholders to offer hands-on learning opportunities.